ANALISIS MANAJEMEN GURU DAN PENDIDIKAN DALAM PENINGKATAN MUTU SEKOLAH - Muhammad Hasan Basari; Nail Ma’aly Wiam; Sifa Dewi Lestari; Zahra Salsabila (JIP: Jurnal Ilmu Pendidikan, 2025)
This article aims to analyze the role of teacher and educational management in improving school quality. The study adopts a qualitative approach with a library research method that integrates theoretical perspectives from Henri Fayol, George Terry, and modern educational management models in Indonesia. The results show that teacher and educational management play a central role in achieving national education standards through processes of planning, organizing, actuating, and controlling (POAC). Effective management supports teacher professionalism, equitable resource allocation, and improved learning outcomes. This study concludes that sustainable educational quality can be achieved through systematic planning, recruitment, development, and evaluation of both educators and education personnel within an integrated management framework